Yield and Yield Parameters Response of Cabbage to Partial Root Drying and Conventional Deficit Irrigation - Halil Demir; Harun Kaman; İlker Sönmez; Ufuk Uçan; İsmail Hakkı Akgün (Agronomy)
Irrigation is one of the most important cultural practices in sustainable cabbage cultivation. While most studies on irrigation in cabbage have focused on conventional deficit irrigation (DI) practices, some plants’ water requirements under the partial root drying (PRD) technique are not yet very clear. In this study, the possible responses of cabbage, such as growth, some quality, yield, yield parameters, water use efficiency (WUE), irrigation water use efficiency (IWUE), and yield response factor (ky), were investigated at four irrigation water levels (125%, 100%, 75%, and 50%) with DI and PRD techniques for 2 years. Irrigation treatments were carried out by the drip irrigation method, and the amount of irrigation water for the control (I-100) was calculated using the measurements taken from the Class-A evaporation container. A total of eight irrigation treatments—four conventional deficit irrigation (I-125, I-100, I-75, I-50) and four partial root drying (PRD-125, PRD-100, PRD75, PRD-50)—were considered in the study. ET values were determined between 47.69–60.78 mm in the first year and 80.11–101.37 mm in the second year. Total and marketable yield values, WUE and IWUE values, were significantly affected by the irrigation treatments. As a result of the research, the highest total and marketable yields were found in I-125, PRD-125, I-100, and PRD-100 treatments. It was important that WUE and IWUE values reached their highest levels in full irrigation and 25% more irrigation treatments as well as in deficit irrigation treatments. In conditions where irrigation water is scarce and expensive, I-75 and PRD-75 applications are also recommended. While an increase in cabbage head height and diameter was observed with increasing irrigation water level, SSC and L values increased at deficit irrigations. According to the correlation coefficients, a positive relationship was determined between marketable yield and head and stem diameter, head height, WUE, and ET for marketable yield. In addition, it was predicted that I-50 and PRD-50 treatments may also be advantageous if the “kc” plant coefficient cover percentage was increased.